The Use of Social Media in Promoting Outbound Tour Packages at PT. Dwidaya World Wide Makassar - Venice Dewi Lestari; Darmayasa Darmayasa; Ilham Junaid (Politeknik Pariwisata Makassar, 2024)
This study aims to: 1). Determine the implementation of social media in promoting outbound tour packages at PT. Dwidaya World Wide Makassar, 2). Knowing the advantages and disadvantages of PT. Dwidaya World Wide Makassar in promoting outbound tour packages. In this study, the data collection technique uses direct communication by asking questions to the resource persons to get information or data. Then a written question related to this research was prepared. Data was collected using qualitative methods: interviews, documentation, and data analysis. The results of the study show that, PT. Dwidaya World Wide implements Facebook and Instagram social media to promote outbound products and tour packages by utilizing social media features. In increasing the promotion of outbound tour packages through social media @dwidaya_tour utilizes Facebook and Instagram features such as photo posts, videos, followers features, hashtags, captions, likes, comments and shares. This feature plays an important role in carrying out promotional activities and building interaction with followers so that it can form more effective promotions. In promoting outbound tour packages, of course, there are advantages and disadvantages on PT. Dwidaya World Wide. The advantages are a large selection of tour packages, a verified Instagram account, a large number of followers and consistency in uploading posts. The disadvantages are that the use of features has not been maximized, the interaction between followers and admins has not been maximized, there are no testimonials and guest documentation. There are several weaknesses of PT. Dwidaya World Wide is no guest travel documentation or testimonials, neither photos nor videos, more featuring templates.